Rice microtubule-associated protein OsMAP65-3.1, but not OsMAP65-3.2, plays a critical role in phragmoplast microtubule organization in cytokinesis - Lin, Xiaoli; Xiao, Yu; Song, Yongping; Gan, Cong; Deng, Xingguang; Wang, Peng; Liu, Jialong; Jiang, Zhishu; Peng, Limei; Zhou, Dahu; He, Xiaopeng; Bian, Jianmin; et al. (Frontiers in Plant Science, 2022)
In plants, MAP65 preferentially cross-links the anti-parallel microtubules (MTs) and plays an important role for cytokinesis. However, the functions of MAP65 isoforms in rice (Oryza sativa. L) are largely unknown. Here, we identified two MAP65-3 homologs in rice, OsMAP65-3.1 and OsMAP65-3.2. We found that both OsMAP65-3.1 and OsMAP65-3.2 were similar in dimerization and location to AtMAP65-3, and the expression of either rice genes driven by the AtMAP65-3 promoter suppressed the cytokinesis failure and growth defect of atmap65-3. However, OsMAP65-3.1 with native promoter also recovered the atmap65-3, but OsMAP65-3.2 with its own promoter had no effects. OsMAP65-3.1 but not OsMAP65-3.2 was actively expressed in tissues enriched with dividing cells. R1R2R3-Myb (MYB3R) transcription factors directly bound to the OsMAP65-3.1 promoter but not that of OsMAP65-3.2. Furthermore, osmap65-3.2 had no obvious phenotype, while either osmap65-3.1 or osmap65-3.1(+/-) was lethal. The eminent MTs around the daughter nuclei and cytokinesis defects were frequently observed in OsMAP65-3.1-defective plants. Taken together, our findings suggest that OsMAP65-3.1, rather than OsMAP65-3.2, plays essential roles in rice cytokinesis resulting from their differential expression which were passably directly regulated by OsMYB3Rs.